2012 Seventh Asia Joint Conference on Information Security 2012
DOI: 10.1109/asiajcis.2012.12
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Security Patch Lifecycle Using Google Trend Tool

Abstract: Information security audit has become more and more important nowadays. Among the audited items, the status of security patch could be the most important part. In this paper, we proposed a security patch lifecycle to assess the information security risk with the help of vulnerability databases. A case study using the Google Trend is also given to demonstrate that the proposed security patch lifecycle is both useful and practical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Rech [15] used GT data to analyze the attention that products received and the cause-effect relation among a few factors in software engineering. Kuo et al [16] demonstrated the lifecycles of internet security systems had the same pattern including four stages: zero day, publicity, cooldown and silence with different scales. The author discovered that GT data showed a interesting correlation with the lifecycle and claimed the reason was that when the vulnerability attracted a lot attention, the risk became large and the lifecycle turned to the decay stages.…”
Section: Related Workmentioning
confidence: 99%
“…Rech [15] used GT data to analyze the attention that products received and the cause-effect relation among a few factors in software engineering. Kuo et al [16] demonstrated the lifecycles of internet security systems had the same pattern including four stages: zero day, publicity, cooldown and silence with different scales. The author discovered that GT data showed a interesting correlation with the lifecycle and claimed the reason was that when the vulnerability attracted a lot attention, the risk became large and the lifecycle turned to the decay stages.…”
Section: Related Workmentioning
confidence: 99%
“…The open ports and their associated applications, OS signatures, and shared network resources all can lead to the vulnerabilities already identified at the national database (Zhang, Caragea, & Ou, 2011), antivirus vendor websites, and hacker community public portals such as the Open Source Vulnerability Database (Kuo, Ruan, Chen, & Lei, 2012). Students learn how to identify these vulnerabilities using online information and special tools and frameworks such as Metasploit (Remirez-Silv & Dacier, 2007).…”
Section: Topic 1: Identify Vulnerabilitiesmentioning
confidence: 99%